Desindustrializaç\~ao: Luzes e sombras no debate brasileiro - Gabriel Coelho Squeff (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper discusses the de-industrialization hypothesis in Brazil based on indicators usually not found in the literature. The evaluation was based on the structure and dynamics of the manufacturing sector vis-à-vis the rest of the economy and, in addition, from an intra-industrial standpoint using OCDE's classification of technological intensity. Both methods allowed us to discuss this subject broadly and accurately, identifying data that support and contradict the hypothesis that Brazil is suffering a de-industrialization process in the negative sense.
Keywords: L60; O10; O14; 330; de-industrialization; manufacturing; technological intensity; Deindustrialisierung; Industrie; Brasilien